Fourth International Open Encounter on Video. - CAYC - Centro de Arte Y Comunicacion, Buenos Aires (Buenos Aires : Centro de Arte y Comunicación, 1975)
Akagawa, Kinji Anthony ; Albright, David ; Alleyn, Edmund ; Alocco, Marcel ; Altmann, Roberto ; Amiard, Bernard ; Anderson, David ; Andrade, Sonia ; Arcodice ; Crivelli, Daniele ; Coppitz, Arrigo ; Arlandi, Gian Franco ; Artworker Foundation ; etc.
Fourth International Open Encounter on Video, CAYC, Buenos Aires, October 31st. to November 14th. 1975
boek